DEVELOPMENT OF MODERN IT AND THEIR IMPACT ON THE DYNAMICS OF CORRUPTION - I. Klyukovskaya; I. Ter-Avanesova (Гуманитарные и юридические исследования)
The article touches upon one of the urgent problems of modern society: the influence of information and communication technologies on social processes. The authors raise the question of the dependence of the level of digitalization of society and the level of corruption crime. The analysis of the degree of influence of modern ICT on the state and dynamics of corruption crime. The subject of the study was statistical data on the indicators of IT use in the world, data on digital literacy ratings and network readiness indices, statistics and reports on the state of crime, and corruption perception indices. The authors focus on the analysis of various aspects of digitalization, correlating with data on corruption crime. The methodological basis of the research is dialectical materialism and general scientiic methods of analysis, synthesis, and others. Formal legal, comparative legal and other legal methods, as well as the method of statistical analysis, were used as special ones. Based on the findings, the authors conclude that progress in the IT field is directly reflected in the state and dynamics of corruption crime, generating a demand in society for improving the means and methods used to combat corruption. The authors have developed an extensive systemic set of measures designed to promote anti-corruption. In conclusion, the article concludes that there is a possibility of a positive impact on corruption crime by modernizing methods of combating it through the use of modern IT tools. It is noted that the systematic implementation of the proposed set of measures, provided they are consistently implemented, will be the irst step towards combating corruption-related crime through information technology, however, achieving this goal is possible only if high-quality systemic digitalization is carried out throughout the country.